PENINGKATAN KETERAMPILAN SISWA SMK NEGERI 9 MAKASSAR MELALUI PEMBUATAN PRODUK SAMOSA IKAN LAYANG - Umniyah Musdhalifah Yusran; Arwita Irawati; Tami Azzahra Nur; Hardianty Askar; Rasdi; Musdalifah; Mujaddid; Leyla Khairunnisa Rifai; Gloria Natalia Christina Siahaan (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service program aimed to enhance the skills and entrepreneurial competence of students at SMK Negeri 9 Makassar through hands-on training in the production of scad fish samosa. The activity employed a participatory approach comprising socialization, demonstration, and direct practice. A pre- and post-training questionnaire was administered to 16 students to assess improvements across five indicators: knowledge of fish diversification, experience in samosa production, ability to produce market-ready products, mastery of samosa-making techniques, and interest in entrepreneurship.  Significant improvements were observed in all indicators. The proportion of students knowledgeable about scad fish diversification increased from 18.75% to 93.75%; all 16 students successfully produced samosa after training compared to zero before. The ability to produce market-ready products rose from 12.5% to 100%, and entrepreneurial interest increased from 50% to 87.5%. The training effectively elevated students’ technical competencies and entrepreneurial awareness, demonstrating the potential of scad fish samosa as a value-added fishery product for school-based enterprise development.